Implementation of the CIPP Evaluation Model in the Kampung Sampah Bernilai (Salai) Program in East Sempaja Village Samarinda - Luthfiyah Nur Azizah; Sri Wahyuni; Wahdatan Nisa; Hepy Triwinarti (SOSIOEDUKASI, 2025)
This study aims to evaluate the Kampung Sampah Bernilai (Salai) Turi Putih program RT 48 East Sempaja Village using the CIPP (Context, Input, Process, Product) evaluation model. This research uses qualitative methods through interviews, observations, and documentation. The data sources come from sorting coordinators and residents who are also waste bank customers. The results of the evaluation show that the context of the program has been in accordance with the needs of the community and received government support. Then in terms of program input, it has involved PKK women, posyandu, dasawisma, and volunteers in planning and implementation even though there are still limited facilities and infrastructure. In the Process, the implementation of the program is participatory through active communication, but there has been no structured evaluation. And in the Product aspect, the program has succeeded in increasing public awareness of the environment and producing useful products from waste. Although the economic impact is still limited, this program is worth continuing and developing by strengthening evaluation, training, and infrastructure support to achieve sustainability and broader impact.